Analysis of the correlation of soil physical attributes with maize grain yield components in different cultivation systems (Research, Society and Development, 2022)
The aim of this work was to analyze the correlation soil physical attributes of the soil with the components of maize grain yield in minimum tillage, conventional tillage and no-tillage systems. An experimental area of ​​approximately 2.13 ha was used, subdivided into three parts, each one receiving a soil management system. At least 150 points were georeferenced in each of the three sub-areas, using an irregular grid, and simple and deformed soil samples were collected at these points. At the defined points, the following attributes were evaluated: gravity moisture, soil density, particle density, total porosity and texture. To evaluate the components of maize yield, the following were measured: number of rows per cob, number of grains per row, number of grains per cob, weight of grains per cob and weight of thousand grains in the sample. Person correlation analysis and geostatistical analysis were performed. The crossed semivariograms satisfactorily reproduced the behavior of the attributes that presented spatial dependence in the same pattern as the simple semivariograms, allowing its use to estimate the weight of grains per maize.